The association between specific activity components and depression in nursing home residents: the importance of the social component. (2nd January 2021) - Knippenberg, Inge A. H.; Reijnders, Jennifer S. A. M.; Gerritsen, Debby L.; Leontjevas, Ruslan
Abstract: Objectives: To longitudinally explore the association between activities and depressive symptoms of nursing home (NH) residents, taking into account that each activity may contain multiple components (physical, creative, social, cognitive, and musical). Method: Study with a baseline and two follow-ups (four and eight months). Participants were forty physically frail residents of four NHs in the Netherlands. Residents were interviewed about depressive symptoms (CES-D) and activities they conducted over the previous week. Three researchers independently rank ordered each activity on the degree to which it could be regarded as having physical, creative, social, cognitive, and musical components. Accounting for the rank score and the time the resident spent on that activity, residents were categorized per activity component into four levels: absent, low, medium, and high. Results: Mixed models predicting depressive symptoms from individual activity components showed significant associations for the social and cognitive components. Compared with the lowest activity level, the analyses showed fewer depressive symptoms for all higher levels of the social and cognitive components. However, a mixed model adjusted for all activity components showed no unique effect of the cognitive component or other components, while the effects of the social component remained significant. The analyses did not show differences between the time points. Conclusion: The results suggest that the effects of activities on depressive symptoms might be mainly explained by their social component. It is, thus, important to always stimulate social involvement and interaction when developing and applying depression interventions. However, intervention research is needed to confirm these findings.